This is marketing You Can't Be Seen Until You Learn To See - Godin, Seth. (New York Portfolio, 2018)
For the first time Seth Godin offers the core of his marketing wisdom in one compact, accessible, timeless package. This is Marketing shows you how to do work you're proud of, whether you're a tech startup founder, a small business owner, or part of a large corporation.
Includes index.
Keywords: Marketing